2024
DOI: 10.1002/wps.21160
|View full text |Cite
|
Sign up to set email alerts
|

The social determinants of mental health and disorder: evidence, prevention and recommendations

James B. Kirkbride,
Deidre M. Anglin,
Ian Colman
et al.

Abstract: People exposed to more unfavourable social circumstances are more vulnerable to poor mental health over their life course, in ways that are often determined by structural factors which generate and perpetuate intergenerational cycles of disadvantage and poor health. Addressing these challenges is an imperative matter of social justice. In this paper we provide a roadmap to address the social determinants that cause mental ill health. Relying as far as possible on high‐quality evidence, we first map out the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 452 publications
0
7
0
Order By: Relevance
“…By emphasizing this relationship, our findings underscore the importance of addressing these interconnected challenges to mitigate the risk of social exclusion. Kirkbride et al [ 16 ] have emphasized the importance of intervening on modifiable social determinants that have an impact on mental health problems and suggested that prevention of social exclusion should start with social determinants to secure adequate living conditions and the economic foundation for social participation. Priebe [ 37 ] goes even further and writes (p. 1): “What should be done?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By emphasizing this relationship, our findings underscore the importance of addressing these interconnected challenges to mitigate the risk of social exclusion. Kirkbride et al [ 16 ] have emphasized the importance of intervening on modifiable social determinants that have an impact on mental health problems and suggested that prevention of social exclusion should start with social determinants to secure adequate living conditions and the economic foundation for social participation. Priebe [ 37 ] goes even further and writes (p. 1): “What should be done?…”
Section: Discussionmentioning
confidence: 99%
“…The directionality of this concept has been challenged by a contradictory representation, known as social causation. In this framework, the process starts with the challenges associated with living in poverty, characterized by economic strain with poor housing, work, and educational conditions and violence and insecurity [ 16 ]. These factors in turn drive behaviors such as the tendency to withdraw from social interaction [ 17 ], including social interaction with family and friends and from other forms of community involvement and participation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, social determinants closely associated with mental health outcomes. 30 Disadvantaged individuals are more vulnerable to mental health conditions, and socio-environmental factors including subcultural contexts and urban-rural difference also correlate with suicide method selection. Strategy focusing on reducing socio-economic inequalities should be a key component of suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…To address the low rates of service use by people with mental disorders, the 2001 World Mental Health Report made ten recommendations, including making mental health treatment more accessible in GMC, making psychotropic drugs more available, educating the public more about mental health, and increasing and improving the training of MHC professionals [9]. As this call for action has been widely adopted [10,11], it is unsurprising that increasing treatment rates for CMDs have been found since [12,13]. However, studies providing up-to-date and more in-depth information on the associations of CMD severity with treatment contact and treatment intensity are lacking, while this knowledge is essential to guide resource allocation.…”
Section: Introductionmentioning
confidence: 99%